Past, Present and Future Compensation Research Perspectives. (September 2015) - Conroy, Samantha A.; Yoon, Yeong Joon; Bamberger, Peter A.; Gerhart, Barry; Gupta, Nina; Nyberg, Anthony J.; Park, Sanghee; Park, Tae-Youn; Shaw, Jason D.; Sturman, Michael C.
Compensation decisions are some of the most important decisions made in organizations, and research in this area has the potential to inform these decisions. Yet compensation has been viewed as a neglected area of HR research. In order to encourage greater quantity and quality of compensation research, this article provides an overview of perspectives of compensation scholars on (1) the future of compensation research, (2) the bridging of individual-level and organization-level compensation research, and (3) the challenges common to publishing compensation research. These comments are based on a professional development workshop conducted at the 2016 Academy of Management meeting focused on encouraging interaction of junior and senior compensation researchers.